Analisis Kestabilan Lereng pada Ruas Jalan Trans Sulawesi Desa Olohuta Kecamatan Kabila, Kabupaten Bone Bolango - Kodung, Mohamad Ashar; Permana, Aang Panji; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2024)
The Trans Sulawesi Road in Olohuta Village, Kabila Bone District, is a crucial route connecting Gorontalo and North Sulawesi. Given the steep roadside slopes, geological analysis and slope stability assessments are essential to prevent landslides that could disrupt access. This study evaluates geological conditions and slope stability using the Rock Mass Rating (RMR), Slope Mass Rating (SMR), and Safety Factor (FK) methods. Geological mapping reveals dacite rock formations within a fault zone, with a Northeast-Southwest structural orientation. RMR analysis classifies slope 1 (RMR = 62) and slope 2 (RMR = 57) as "good." SMR analysis indicates partial stability, with slope 1 experiencing Direct Toppling (20.47%) and slope 2 undergoing Flexural Toppling (18.52%), resulting in SMR values of 58.25 and 53.25, respectively. The Bishop Method shows low safety factors, with values of 0.59 for slope 1 and 0.56 for slope 2, indicating instability. To improve slope stability, this study recommends modifying slope geometry.